Effectiveness and safety of recombinant zoster vaccine: A review of real-world evidence - Raunak Parikh; David Singer; Elizabeth Chmielewski-Yee; Christophe Dessart (Taylor & Francis Group, 2023)
ABSTRACTThe recombinant zoster vaccine (RZV) was licensed in the US for prevention of herpes zoster (HZ) in 2017. We conducted a literature search (January 1, 2017-August 1, 2023) using PubMed, Embase, and Scopus to consolidate the real-world evidence related to RZV. Overall, RZV effectiveness against HZ was high across the studied populations in real-world settings, including adults aged ≥ 50 years and patients aged ≥ 18 years with immunodeficiency or immunosuppression. Effectiveness was higher with two doses versus one dose, especially in elderly people and immunocompromised individuals. The safety profile of RZV was broadly consistent with that established in clinical trials. RZV does not appear to increase the risk of disease flares in patients with immune-mediated diseases. Approximately two-thirds of individuals received a second RZV dose within 2-6 months after the first dose. Collectively, RZV effectiveness against HZ was high, and these real-world studies reaffirm its favorable benefit-risk profile.